Designing a Framework of Components to Support Patient Engagement in Research - Öfelein, Matthias; Reichold, Michael; Maier, Christian; Prokosch, Hans-Ulrich (German Medical Data Sciences: Shaping Change – Creative Solutions for Innovative Medicine, 2019)
In the context of the German Medical Informatics Initiative (MII), where data reuse and data sharing are major goals, cross-site, long-term research on patient care data can only be conducted lawfully with informed patient consent. Thus, the MII consent working group developed a template form for patient information and broad consent based on work that has been done for a former biobank project. The broad consent enables the patient to consent to the use of a wide range of the documented data including research purposes. Therefore, a user-friendly tool is needed which not only supports the storage and maintenance of the patient's consents but also allows him to easily review or withdraw his consents. Furthermore, the tool should allow the patient to review the use of his data in research projects and possible publications. This is why we developed a concept of how such a tool could be integrated into the clinical and research system landscape and implemented a prototype as a proof of concept.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Consent Management; Data Sharing; Informed Consent; Patient Participation

Designing and Implementing an IT Architecture for a Digital Multicenter Dementia Registry: DigiDEM Bayern - Reichold, Michael; Dietzel, Nikolas; Chmelirsch, Christina; Kolominsky-Rabas, Peter; Grässel, Elmar; Prokosch, Hans-Ulrich (Applied Clinical Informatics, 2021)
Background Registries are an essential research tool to investigate the long-term course of diseases and their impact on the affected. The project digiDEM Bayern will set up a prospective dementia registry to collect long-term data of people with dementia and their caregivers in Bavaria (Germany) supported by more than 300 research partners. Objective The objective of this article is to outline an information technology (IT) architecture for the integration of a registry and comprehensive participant management in a dementia study. Measures to ensure high data quality, study governance, along with data privacy, and security are to be included in the architecture. Methods The architecture was developed based on an iterative, stakeholder-oriented process. The development was inspired by the Twin Peaks Model that focuses on the codevelopment of requirements and architecture. We gradually moved from a general to a detailed understanding of both the requirements and design through a series of iterations. The experience learned from the pilot phase was integrated into a further iterative process of continuous improvement of the architecture. Results The infrastructure provides a standardized workflow to support the electronic data collection and trace each participant's study process. Therefore, the implementation consists of three systems: (1) electronic data capture system for Web-based or offline app-based data collection; (2) participant management system for the administration of the identity data of participants and research partners as well as of the overall study governance process; and (3) videoconferencing software for conducting interviews online. First experiences in the pilot phase have proven the feasibility of the framework. Conclusion This article outlines an IT architecture to integrate a registry and participant management in a dementia research project. The framework was discussed and developed with the involvement of numerous stakeholders. Due to its adaptability of used software systems, a transfer to other projects should be easily possible.
CRIS-Team Scopus Importer:2021-06-25
Keywords: data collection; dementia; participant management; registries; research planning and conduct; workflow

Digital Dementia Registry Bavaria - DigiDEM Bayern: Study protocol for a multicentre, prospective, longitudinal register study - Dietzel, Nikolas; Kürten, Lara; Karrer, Linda; Reichold, Michael; Köhler, Laura; Nagel, Andreas; Chmelirsch, Christina; Seebahn, Kathrin; Hladik, Markus; Meuer, Sebastian; Kirchner, Anna; Holm, Kristina; et al. (BMJ Open, 2021)
Introduction Dementia is one of the most relevant widespread diseases, with a prevalence of currently 50 million people with dementia worldwide. The care of people with dementia will be one of the major challenges for healthcare systems worldwide. Digitalisation offers new possibilities to improve both dementia healthcare and health outcomes research as a fundament for national healthcare planning. The a € Digital Dementia Registry Bavaria - digiDEM Bayern' aims to improve the understanding of the complexity and long-term progression of dementia and the current care situation in Bavaria. Moreover, by offering digital services, digiDEM will actively contribute to improving the care situation in Bavaria. Methods and analysis digiDEM will recruit people with dementia and their family caregivers in all administrative regions of Bavaria. All participants will undergo dementia screening prior to study inclusion in order to identify people with mild cognitive impairment and mild-to-moderate dementia. Participants will be followed up over a period of three years. Sociodemographic data, type of dementia, symptoms, diagnosis, cognitive trajectories, activities of daily living, behavioural and psychological symptoms, falls, resource utilisation, caregiver burden, quality of life, needs of people with dementia and their caregivers, mobility, use of media and sources of information will be assessed. The project will implement a digital web-based platform for data collection. Data will be collected by means of standardised online or face-to-face interviews. Ethics and dissemination The study obtained ethical approval from the Ethics Committee of the Medical Faculty of Friedrich-Alexander-University Erlangen-Nürnberg (FAU) (application number: 253_20 B). Findings will be used for evidence-based decision-making for health decision-makers in order to optimise dementia healthcare in the state of Bavaria. Specific analyses will be conducted for the participating research partners. Results of the study will be published in peer-reviewed journals.
CRIS-Team Scopus Importer:2021-02-26
Keywords: dementia; neurology; public health

EHealth Interventions for Dementia Using WordPress Plugins as a Flexible Dissemination for Dementia Service Providers - Reichold, Michael; Selau, Marina; Grässel, Elmar; Kolominsky-Rabas, Peter; Prokosch, Hans-Ulrich (Studies in Health Technology and Informatics, 2021)
The benefits of eHealth interventions for people with dementia and their informal caregivers have been demonstrated in several studies. In times of contact restrictions, digital solutions have become increasingly important, especially for people with dementia and their mostly elderly caregiving relatives, which are at increased risk of severe illness from COVID-19. As in many other health areas, there is a lack of digital interventions in the dementia landscape that are successfully implemented (i.e., put into practice), especially digital interventions that are scientifically evaluated. Evaluated and proven effective digital interventions exist, but these often do not find their way from research into practice and stay on low-level implementation readiness. Within the project digiDEM Bayern, a digital platform with digital services and interventions for people affected by dementia (people with dementia, caregivers, volunteers and interested citizens) is established. As one digital intervention for informal caregivers, the Angehörigenampel (caregivers' traffic-light) was developed, which is able to assess the physical and psychological burden of caregivers. This can help to counteract the health effects of caregiving burden early on before it is too late. The development of the digital intervention as a WordPress-plugin was kept generic so that it can easily be adapted to other languages on further websites. The intervention as a plugin' approach demonstrates an easy and flexible way of deploying eHealth interventions to other service providers, especially from other countries. The implementation barriers for other service providers are low enough for them to be able to easily integrate the eHealth intervention on their website, enabling more caregivers to benefit from the disseminated eHealth intervention.
CRIS-Team Scopus Importer:2021-06-04

Stakeholder perspectives on the key components of a digital service platform supporting dementia - Digidem Bayern - Reichold, Michael; Dietzel, Nikolas; Karrer, Linda; Grässel, Elmar; Kolominsky-Rabas, Peter; Prokosch, Hans-Ulrich (Studies in Health Technology and Informatics, 2020)
The increasing number of people with dementia and caregiving relatives will require a change in the provision of dementia-related services in the future. Digital technologies are a force for change. The new project digiDEM Bayern with its digital services on a digital platform and a digital patient registry should help to improve the situation for people with dementia and their caregivers especially in rural settings. An online survey among service providers for people with dementia and caregiving relatives in Bavaria was conducted to find out how they assess the current landscape of digital and non-digital service offers for people with dementia and their caregivers. The results of the survey have revealed that there is currently a large gap in the provision of digital services varying between the different categories surveyed. digiDEM Bayern addresses this gap with its digital dementia-related service platform.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Dementia; Digital; Informal caregiver; Platform; Services; Stakeholder

Usability evaluation of an offline electronic data capture app in a prospective multicenter dementia registry (digidem bayern): Mixed method study - Reichold, Michael; Heß, Miriam; Kolominsky-Rabas, Peter; Grässel, Elmar; Prokosch, Hans-Ulrich (JMIR Formative Research, 2021)
Background: Digital registries have been shown to provide an efficient way of gaining a better understanding of the clinical complexity and long-term progression of diseases. The paperless method of electronic data capture (EDC) during a patient interview saves both time and resources. In the prospective multicenter project "Digital Dementia Registry Bavaria (digiDEM Bayern)," interviews are also performed on site in rural areas with unreliable internet connectivity. It must be ensured that EDC can still be performed in such a context and that there is no need to fall back on paper-based questionnaires. In addition to a web-based data collection solution, the EDC system REDCap (Research Electronic Data Capture) offers the option to collect data offline via an app and to synchronize it afterward. Objective: The aim of this study was to evaluate the usability of the REDCap app as an offline EDC option for a lay user group and to examine the necessary technology acceptance of using mobile devices for data collection. The feasibility of the app-based offline data collection in the digiDEM Bayern dementia registry project was then evaluated before going live. Methods: An exploratory mixed method design was employed in the form of an on-site usability test with the "Thinking Aloud" method combined with an online questionnaire including the System Usability Scale (SUS). The acceptance of mobile devices for data collection was surveyed based on five categories of the technology acceptance model. Results: Using the "Thinking Aloud" method, usability issues were identified and solutions were accordingly derived. Evaluation of the REDCap app resulted in a SUS score of 74, which represents "good" usability. After evaluating the technology acceptance questionnaire, it can be concluded that the lay user group is open to mobile devices as interview tools. Conclusions: The usability evaluation results show that a lay user group generally agree that data collecting partners in the digiDEM project can handle the REDCap app well. The usability evaluation provided statements about positive aspects and could also identify usability issues relating to the REDCap app. In addition, the current technology acceptance in the sample showed that heterogeneous groups of different ages with diverse experiences in handling mobile devices are also ready for the use of app-based EDC systems. Based on these results, it can be assumed that the offline use of an app-based EDC system on mobile devices is a viable solution for collecting data in a decentralized registry-based research project.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Dementia; Digital health; Electronic data collection; Evaluation; Mobile app; Mobile device; Offline; Registry; Usability; Usability testing